Die Entwicklung der sozialwissenschaftlichen Diskussion über Schulabsentismus in Japan: Neue Trends oder ein altes Phänomen? - Kreitz-Sandberg, Susanne; Lesch, Vincent B. (Japan 2019, 2019)
The Development of Social Science Discussions on School Absenteeism in Japan: New Trends or an Old Problem? The aim of this paper is to summarize the development of the social science discourse on school absenteeism (futōkō) in Japan and to analyze it in the context of the debate on social inequality in society (kakusa shakai). This systematic literature review will answer the question: how has the issue of school absenteeism in Japan developed since the post-war period up to the present? School absenteeism has been a subject of much discussion in Japan since the 1960s, and this paper discusses whether recent research on school absenteeism is merely examining this phenomenon from old perspectives or identifying new trends that are also interesting from an international viewpoint. As a background, this paper clarifies central Japanese terms in research on absenteeism since the post-war period and describes how refusal to attend school has been considered as school and youth problems since the 1980s. The article builds on a methodology that is often referred to as desk research, which has undergone a renaissance under the concept of systematic literature studies where search strategies and the presentation of the results are formalized in order to ensure the transparency and reliability of the information. The research focuses on Japanese and international publications of the last decade. The evaluation of a total of 22 selected articles (including journal articles and book chapters) reveals important topics, such as new potential risk groups and solution strategies. The articles show absenteeism and high school drop-out are more frequent for disadvantaged groups in connection to poverty, migration, sexual identity and psychosocial factors. Interestingly, in the literature, connections between futōkō and social withdrawal (hikikomori) have been described as an overlapping but still different phenomena. Another trend that has been highlighted in the literature is the role of various new actors in and around the school system. Although school absenteeism may appear to be an old problem in Japanese research, the role of new players in the education system and the diversification of the Japanese school landscape are becoming more apparent in response to persistently high levels of absenteeism.
Keywords: Sozialwissenschaften; Erforschung; Schulversäumnis; Schule; Japan